Empowering Employees through Green HRM: Fostering Eco-Friendly Tourism in Semarang Regency - Dyan Triana Putra; Dyah Palupiningtyas; Krisnawati Setyaningrum Nugraheni; Julian Andriani Putri; Febe Humble Kristanto (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
This study examines the role of Green Human Resource Management (GHRM) in increasing employee awareness and participation in eco-friendly tourism management in Semarang Regency. Using a mixed-methods approach, this research analyzes the implementation of GHRM practices, evaluates the level of employee awareness and participation, tests the influence of GHRM on employee awareness and participation, and identifies factors affecting GHRM effectiveness. The results show that GHRM practices, especially green training and development and green employee involvement, significantly predict employee awareness and participation levels in environmentally friendly practices. However, the implementation of GHRM in the Semarang Regency tourism industry is still not optimal and faces various challenges. A more contextual, participatory, and integrated approach is needed to optimize the role of GHRM in supporting sustainable tourism. Practical implications of this research include the need to integrate sustainability principles into all HR functions, design relevant training programs, involve employees in GHRM initiatives, align reward systems with sustainability goals, and develop an organizational culture that supports sustainability. This study provides valuable insights into the role of GHRM in realizing sustainable tourism and contributes to achieving the Sustainable Development Goals.